2019
DOI: 10.1002/ejp.1349
|View full text |Cite
|
Sign up to set email alerts
|

Propofol attenuates postoperative hyperalgesia via regulating spinal GluN2B‐p38MAPK/EPAC1 pathway in an animal model of postoperative pain

Abstract: Background Total intravenous anesthesia with propofol has been shown to reduce postoperative pain in some clinical studies, but knowledge of its underlying analgesic mechanism remains limited. In this study, we compared the analgesic effects of propofol versus isoflurane in an animal model of postoperative pain and evaluated its underlying molecular mechanisms. Methods Plantar incision was made in the hind paws of rats under general anesthesia with 2.5% of inhalational isoflurane (isoflurane group) or intraven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…21,30 Defined spinal cord mechanisms of propofol and pentobarbital antinociception have been suggested for both drugs, and limited clinical data suggests reduced postoperative pain following intraoperative propofol treatment, compared with sevoflurane. 11,62,70,74,86,94 Preclinical rodent findings suggest that both propofol and pentobarbital possess significant, intrinsic antinociceptive efficacy. However, the current findings in NHP demonstrated that sedating doses of either propofol or pentobarbital did not suppress noxious pressure activation of SII/Ins.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…21,30 Defined spinal cord mechanisms of propofol and pentobarbital antinociception have been suggested for both drugs, and limited clinical data suggests reduced postoperative pain following intraoperative propofol treatment, compared with sevoflurane. 11,62,70,74,86,94 Preclinical rodent findings suggest that both propofol and pentobarbital possess significant, intrinsic antinociceptive efficacy. However, the current findings in NHP demonstrated that sedating doses of either propofol or pentobarbital did not suppress noxious pressure activation of SII/Ins.…”
Section: Discussionmentioning
confidence: 99%
“…4,26,27,34,64 Data from rodent studies suggest that sedative doses of propofol, both 36 and 90 mg/kg/hr., are antinociceptive. 74,94 It is possible that propofol's analgesic effect in NHP could be observed at doses that are higher than that needed for stable sedation, which would be, in macaques, between 12 to 36 mg/ kg/hr. 34 The current study tested the effects of 20 and 30 mg/ kg/hr propofol on noxious stimulus-evoked brain activation.…”
Section: Methodsmentioning
confidence: 99%
“…A paucity of studies has demonstrated that Epac1 is involved in the inflammation‐induced nociception. With pre‐clinical neuropathic or chronic pain model, Epac1 facilitated the hyperalgesia via multiple signaling pathways, for example, Rap1, PLC, PLD, MEK/ERK, GRK2, PKCα, and PKCε 19,20,44–47 . However, most of these studies only explore the Epac mechanism in pain on peripheral tissues or organs, especially dorsal root ganglion.…”
Section: Discussionmentioning
confidence: 99%
“…Another potential mechanism may be via propofol’s effect on the exchange protein directly activated by cAMP (EPAC). EPAC is involved in the transition from acute to persistent pain, and propofol has been shown to reduce spinal dorsal horn EPAC1 expression in an animal model for postoperative pain [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%